Forest Therapy. The challenge of the future for the project of living environments - Ornella Zerlenga; Valeria Menchetelli; Alex Gesse (Disegnare con)
DOI: https://doi.org/10.20365/disegnarecon.33.2024.ed <!--EndFragment-->